1995 IEEE Ultrasonics Symposium. Proceedings. An International Symposium
DOI: 10.1109/ultsym.1995.495787
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine scale piezoelectric composite materials for high frequency ultrasonic imaging arrays

Abstract: Intravascular and endoscopic acoustic imaging typically require high ultrasonic operating frequencies, over 7 MHz. At these frequencies the ceramic transducer dimensions become very small; pitches in the order of 20 to EOpm are existing interconnect approaches and be fabricated at low needed. Moreover, such arrays must be compatible with cost. These piezoelectric transducer array requirements severely challenge the ability of conventional ET ceramic technologies in terms of cost-effective fabrication.To meet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
6
0
3
Order By: Relevance
“…For example, Stevenson et al 15 reported PZT elements 20 m thick produced by laminating sintered tape cast sheets. Injection molding method have been developed 16 capable of producing features on the order of 22 m.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Stevenson et al 15 reported PZT elements 20 m thick produced by laminating sintered tape cast sheets. Injection molding method have been developed 16 capable of producing features on the order of 22 m.…”
Section: Discussionmentioning
confidence: 99%
“…recently there have been some successful attempts to increase the operating frequency of composites using conventional dice-and-fill techniques [8], injection molding [9], laser micromachining [10], and interdigital pair bonding [11], as well as deep reactive ion etching of single-crystal materials [12]. However, although these techniques suffice to make standard medical imaging transducers and research devices operating up to 40 MHz, the fabrication of the composites becomes very difficult at higher frequencies because of the ultrafine lateral features required for efficient operation, and design compromises must be introduced, for example, relating to ceramic volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Após a cura do polímero, o compósito é aquecido, e é aplicado um forte campo elétrico (da ordem de kV/mm) para polarizar as partículas de material piezelétrico. Para construir compósitos com conectividade 1-3 e 2-2 em larga escala, é geralmente utilizado moldagem por injeção (PAZOL et al, 1995). Nesse processo é misturado pó de material piezelétrico com uma espécie de cola e em seguida a mistura é colocada num molde previamente fabricado.…”
Section: Construção De Materiais Piezelétricos Compósitosunclassified